2012
DOI: 10.1016/j.watres.2012.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of neonicotinoid insecticides with carbonate radicals

Abstract: The reaction of three chloronicotinoid insecticides, namely Imidacloprid (IMD), Thiacloprid (THIA) and Acetamiprid (ACT), with carbonate radicals (CO3*-) was investigated. The second order rate constants (4 ± 1)×106, (2.8 ± 0.5)×105, and (1.5 ± 1)×105 M-1s-1 were determined for IMD, THIA and ACT, respectively. The absorption spectra of the organic intermediates formed after CO3*-attack -aminoalkyl radicals. A reaction mechanism involving an initial charge transfer from the amidine nitrogen of the insecticides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(27 citation statements)
references
References 41 publications
0
24
0
3
Order By: Relevance
“…Dell'Arciprete et al [24,25] used SO4  and CO3  radical anions for imidacloprid (and two other neonicotinoids) oxidation, while Kosno et al [23] oxidized nicotine by N3  radicals.…”
Section: Pulse Radiolysis Experimentsmentioning
confidence: 99%
“…Dell'Arciprete et al [24,25] used SO4  and CO3  radical anions for imidacloprid (and two other neonicotinoids) oxidation, while Kosno et al [23] oxidized nicotine by N3  radicals.…”
Section: Pulse Radiolysis Experimentsmentioning
confidence: 99%
“…Therefore, relatively higher produced. It has been reported that CO 3 ÅÀ is also highly reactive species with a redox potential of 1.78 V [35]. Since CO 3 ÅÀ is capable of oxidizing many organic pollutants efficiently, solutions containing CO 3 2À or HCO 3 À ions showed a less inhibitory impact on atrazine degradation.…”
Section: Effect Of Common Inorganic Anions Humic Acid and Chloroformmentioning
confidence: 99%
“…Dell'Arciprete et al [14] reported that thiacloprid (and generally the chloronicotinoid insecticides) shows low reactivity towards carbonate radicals. Their reaction rate constants (k(THIA + • OH ) = 7.5 × 10 10 L mol -1 s -1 and k(THIA + CO 3…”
Section: Introductionmentioning
confidence: 99%
“…•− ) = 2.8 × 10 5 L mol -1 s -1 ) were obtained using flash photolysis, however, the former rate constant seems to be unrealistic, since it is half of an order of magnitude higher than the diffusion limited value [14,15].…”
Section: Introductionmentioning
confidence: 99%